Reproductive aspects of the velvet belly lantern shark Etmopterus spinax (Condrichthyes: Etmopteridae), from the central western Mediterranean sea. Notes on gametogenesis and oviducal gland microstructure. - PORCU, C.; MARONGIU, M. F.; FOLLESA, M. C.; BELLODI, A.; MULAS, A.; PESCI, P.; CAU, A. (Mediterranean Marine Science, 2013)
In this paper, the reproductive biology of the velvet belly lanternshark Etmopterus spinax was analyzed in Sardinian waters (central western Mediterranean). This species was sexually dimorphic with females growing to a larger size than males. Marked sexual dimorphism in size was also observed along the vertical gradient. Histological analysis of gonads was very useful in assigning macroscopical maturity stages. The investigation on the microstructure of oviducal gland (OG) highlighted four morphofunctional zones with mucous and/or proteic secretions according to the zone and to their specific functions and development. Sperm in the OG was found for the first time in E. spinax. The localization of sperm storage tubules deeper in OG suggested long-term sperm storage, which is in agreement with the long reproductive cycle described. This species matured late, specifically at 80.7% and 79% at the maximum observed size for females and males respectively. Mature specimens were found throughout the year with pregnant females observed in winter and autumn. A low fecundity was observed with a mean ovarian fecundity of 16.5 mature follicles.